Do Information Technology and Human Resources Create Business Performance? The Role of Consumer Preferences - Almaududi Ausat, Abu Muna; Judijanto, Loso; Ayesha, Ivonne; Rijal, Syamsu; Saranani, Fajar (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractInformation technology is now a key pillar in an organization's business strategy to achieve optimal profits. Consumer changes and preferences play a central role in the development and adjustment of information technology to meet fluctuating market demands. The success of achieving the company's vision and mission is highly dependent on human resources who excel in the IT field. This research aims to review the importance of IT and HR in achieving the ideal vision and mission that has been planned. This research focuses on descriptive qualitative research that explores previous studies on IT, HR, consumer change, preferences, and business performance. Relevant data surrounding these variables were collected, summarized, and analyzed. The results confirmed that IT and HR play a crucial role in improving business performance. These factors must be combined holistically to achieve competitive advantage and sustainable long-term business performance, especially in the face of dynamic consumer changes and preferences. Keywords: IT, HR, business performance, consumer preferences